Internalization of Pancasila Values Through Islamic Religious Education at MTS Ma’arif 31 Trimurjo - Eko Wahyu Dono; Hernisawati Hernisawati; Rinamida Hayati (CV. Edutechnium Indonesia, 2025)
The research was conducted at MTs Ma’arif 31 Trimurjo, Central Lampung, focusing on the internalization of Pancasila values through Islamic Religious Education. Pancasila, as the foundation of the Indonesian state, consists of five fundamental principles that guide national identity and unity. The integration of these values within Islamic Religious Education plays a vital role in shaping students’ character. Islamic Religious Education holds a fundamental position in moral development, aiming to instill ethical values based on the Qur'an and As-Sunnah. Through this education, students learn to understand, practice, and implement Islamic teachings in their daily lives. This process not only strengthens their faith but also aligns their behavior with national values. By internalizing Pancasila through Islamic teachings, students at MTs Ma’arif 31 Trimurjo develop into individuals with strong moral character, responsibility, and social awareness. This approach ensures that they uphold national unity while maintaining their religious identity. Ultimately, the application of Pancasila values in their environment contributes to the formation of high-quality individuals who embody both Islamic and national principles.